Adapting re‐usable elastomeric respirators to utilise anaesthesia circuit filters using a 3D‐printed adaptor ‐ a potential alternative to address N95 shortages during the COVID‐19 pandemic. (26th May 2020) - Liu, D. C. Y.; Koo, T. H.; Wong, J. K. K.; Wong, Y. H.; Fung, K. S. C.; Chan, Y.; Lim, H. S.
Summary: The COVID‐19 pandemic has increased the demand for disposable N95 respirators. Re‐usable elastomeric respirators may provide a suitable alternative. Proprietary elastomeric respirator filters may become depleted as demand increases. An alternative may be the virus/bacterial filters used in anaesthesia circuits, if they can be adequately fitted onto the elastomeric respirators. In addition, many re‐usable elastomeric respirators do not filter exhaled breaths. If used for sterile procedures, this would also require modification. We designed a 3D‐printed adaptor that permits elastomeric respirators to interface with anaesthesia circuit filters and created a simple modification to divert exhaled breaths through the filter. We conducted a feasibility study evaluating the performance of our modified elastomeric respirators. A convenience sample of eight volunteers was recruited. Quantitative fit testing, respiratory rate and end‐tidal carbon dioxide were recorded during fit testing exercises and after 1 h of wear. All eight volunteers obtained excellent quantitative fit testing throughout the trial. The mean (SD) end‐tidal carbon dioxide was 4.5 (0.5) kPa and 4.6 (0.4) kPa at baseline and after 1 h of wear (p = 0.148). The mean (SD) respiratory rate was 17 (4) breaths.min −1 and 17 (3) breaths.min −1 at baseline and after 1 h of wear (p = 0.435). Four out of eight subjects self‐reported discomfort; two reported facial pressure, one reported exhalation resistance and one reported transient dizziness on exertion. Re‐usable elastomeric respirators to utilise anaesthesia circuit filters through a 3D‐printed adaptor may be a potential alternative to disposable N95 respirators during the COVID‐19 pandemic.